Young women in science and technology: The importance of choice - Angeliki Dimitriadi (Journal of Innovation and Entrepreneurship, 2013)
Despite significant improvements in the last couple of years, women are still under-represented in science and technology, both in the academic and private sector. This is due to a variety of reasons, mostly related to the role allocated to women in modern society as well as pre-existing prejudices that form glass ceilings while encouraging male presence in the workplace. It is also however, a result of information or lack of, which places young women in difficult position of making a career choice, with little knowledge of available possibilities. What seems to be missing are good role models that could act as inspiration and source of information and guidance, and offer a glimpse into the reality of being a female employed in the field of science and/or technology. Parents, teachers, and career guidance counselors all have a significant role in assisting or hindering the way young women chose their career paths and that choice begins early on from school, all the way through to higher education. Choice, essentially, and factors that determine it as well - as ways of encouraging female participation in science and technology - are the focus of the present article, which is based on results from the European project Information for a choice: empowering young women through learning for scientific and technological career paths, realized under the 6th Framework Program. As this article will show, the promotion through the usage of new technologies, of role models, is crucial in breaking the existing stereotype of women in science, engineering and technology. Science is often rejected as a career choice due to limited information available and positive role models to encourage young girls in participating. Career orientation offered at school through the usage of new technologies is an important step in that direction; however, particularly in countries where the family unit is especially influential in career decisions, parents must be brought in and educated on the possibilities available. Mass media also play an important role in introducing and sustaining stereotypical images of women in particular professional roles, thus, any outreach solutions need to include them.
Keywords: 650; science and technology; role models; stereotypes; transferability